Synthesis of ZSM-5 Zeolite from Metakaolin and Rice Husk Ash to CO2 Adsorption. (21st January 2021) - Klunk, Marcos Antonio; Das, Mohuli; Dasgupta, Sudipta; Caetano, Nattan Roberto; Xavier, Soyane Juceli Siqueira; de Souza, Débora Machado; Wander, Paulo Roberto; Moraes, Carlos Alberto Mendes
Abstract : Several mitigation processes involving carbon dioxide injection into adsorbent materials such as zeolites, are currently very popular as research studies. The objective of our present work is to apply the green synthesis method of molecular sieve with rice husk ash and metakaolin in four individual Si/Al ratios (20, 40, 60 and 80). The micrographs obtained with the aid of SEM (sample 80-ZSM-5) revealed a spherical morphology with aggregated particles. Analysis executed with EDS (Energy Dispersive Spectroscopy) confirmed the presence of Si, Al, O, K and Na. X-ray diffraction helped in the identification of crystalline phases related to the structures of zeolites mordenite and ZSM-5 (mostly). The zeolitic materials were tested for CO2 adsorption assays. The results demonstrated a considerable capacity of CO2 adsorption by 6.5 mmol g −1 of adsorbent at the pressure of 9 bar. Therefore, this research establishes zeolites of ZSM-5 type to be promising as adsorbents for CO2 capture.